Réponses

2014-06-15T11:24:12+02:00
Calculer S dans chacun des cas suivants :

S = b - (a + d) - c
a)
a = 10 ; b = 4 ; c = 6 ; d = - 8
S = 4 - (10 + - 8) - 6
S = 4 - (10 - 8) - 6
S = 4 - 10 + 8 - 6
S = 4 + 8 - 10 - 6
S = 12 - 16
S = - 4

b)
a = - 7 ; b = 3 ; c = - 1 ; d  = 2
S = 3 - (- 7 + 2) - - 1
S = 3 + 7 - 2 + 1
S = 11 - 2
S = 9

c)
a = - 6 ; b = 7 ; c = - 3 ; d = - 10
S = 7 - (- 6 + - 10) - - 8
S = 7 - (- 6 - 10) + 8
S = 7 + 6 + 10 + 8
S = 7 + 6 + 10 + 8
S = 31

2014-06-15T11:58:57+02:00
S = b - (a + d) - c = b - a - d - c
a)  S  = b - a - d - c
a = 10 ; b = 4 ; c = 6 ; d = - 8
S = 4 - 10 - (- 8) - 6
S = 4 - 10 + 8 - 6
S = 4 + 8 - 10 - 6
S = 12 - 16
S = - 4

b) S  = b - a - d - c
a = - 7 ; b = 3 ; c = - 1 ; d  = 2
S = 3 - (- 7) - 2 - (-1)
S = 3 + 7 - 2 + 1
S = 11 - 2
S = 9

c) S  = b - a - d - c
a = - 6 ; b = 7 ; c = - 3 ; d = - 10
S = 7 - (-6) - (-10) - (-3)
S = 7 + 6 + 10 + 3
S = 7 + 6 + 10 + 3 
S = 26